Edutainment "Aritmo": Development and Impact of Video Games on Students' Critical Thinking Skills - Ningtiyas, Fitri Ayu; Mahmuzah, Rifaatul; Zahara, Yulia; Sinaga, Nurul Afni (JDIME: Journal of Development and Innovation in Mathematics Education, 2024)
This study aims to develop and evaluate the effectiveness of a video game-based learning media in enhancing students' critical thinking skills in social arithmetic. The research and development (R&D) method, utilizing the Borg and Gall model, was employed to produce valid, practical, and effective learning media. The research instruments included validation sheets, practicality questionnaires, and effectiveness tests. The sample was selected using purposive sampling, involving 120 respondents from two different junior high schools. The respondents consisted of five experts as validators, 60 students who used the "Aritmo" video game-based learning media, and 60 students as the control group. The validation results by the experts indicated that the "Aritmo" video game has a very high quality, with an average score of 4.6 for alignment with learning objectives and user engagement, 4.4 for content appropriateness and functionality, and 4.0 and 4.2 for graphics and ease of use, respectively. The material validation also showed satisfactory results, with an average score of 4.4 for curriculum alignment, 4.6 for content accuracy, and 4.2 for relevance to learning objectives. The effectiveness test results, using an independent sample t-test, revealed that the use of the "Aritmo" video game had a significant impact on improving students' critical thinking skills, with a Sig. value of 0.031, which is lower than the significance level of 0.05. Thus, this study concludes that the "Aritmo" video game is an effective learning medium that can be used to enhance students' critical thinking skills in social arithmetic learning.